2012
DOI: 10.5304/jafscd.2012.031.003
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Heavy Metals and Pesticide Residues in Leafy Vegetables and Implications for Peri-urban Farming in Nairobi, Kenya

Abstract: The primary objective of this study was to assess the levels of heavy metals, nitrate, and pesticide residues in kale (Brassicaolaracea var. olecephala), a leafy vegetable. The study was conducted in three peri-urban sites in Nairobi, Kenya, where the use of wastewater irrigation is pervasive. The results indicated elevated levels of boron (B), cobalt (Co), chromium (Cr), copper (Cu), lead (Pb), zinc (Zn) and nickel (Ni) in vegetables irrigated with wastewater in two sites. High loadings of the heavy metals Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Botanical names, common names, local names and parts of the Medicinal plants used in the study The ve plant species with As concentrations of <0.2 mg/kg from both study regions were W. ugandensis, V. auriculifera, M. indica, A. abyssinica and A. hockii. The plants could be releasing low amounts of arsenic to the body of the plant As are similar to those in different ora of less than 0.01 to 0.4 mg/kg reported by different authors(Karanja et al 2012;Zhu et al 2013) Tadesse et al (2019). reported As levels in different plants collected from Awash river basin in Ethiopia as ranging from not detected to 0.009 mg/kg.…”
supporting
confidence: 83%
“…Botanical names, common names, local names and parts of the Medicinal plants used in the study The ve plant species with As concentrations of <0.2 mg/kg from both study regions were W. ugandensis, V. auriculifera, M. indica, A. abyssinica and A. hockii. The plants could be releasing low amounts of arsenic to the body of the plant As are similar to those in different ora of less than 0.01 to 0.4 mg/kg reported by different authors(Karanja et al 2012;Zhu et al 2013) Tadesse et al (2019). reported As levels in different plants collected from Awash river basin in Ethiopia as ranging from not detected to 0.009 mg/kg.…”
supporting
confidence: 83%
“…At the same time, the tolerance of most AIVs to a wide spectrum of abiotic and biotic stresses makes them more suited to smallholders' low-input production techniques than their exotic counterparts, which frequently require pesticides and fertilizers and an adequate supply of water to perform well. Interest in AIVs is being further driven by health consciousness among the more affluent urban consumers who associate these vegetables with a low risk of pesticide and pathogen contamination (Karanja, Njenga, Mutua, Lagerkvist, Kutto, & Okello, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were made in other countries in the subregion. For instance, in Kenya, Karanja et al [18] found excessive levels of diazinon, profenofos, and cypermethrin in leafy vegetables. However, in Benin, similar concentrations of dichlorodiphényltrichloroéthane and lindane were found in samples by Diop et al [13].…”
Section: Discussionmentioning
confidence: 99%